Evaluation of High-Dose Isoniazid in Multidrug-Resistant Tuberculosis Treatment - Gerussi, Valentina; Petersen, Tania; Bonnet, Isabelle; Aubry, Alexandra; Bachir, Marwa; Gyde, Esther; Morel, Florence; Poignon, Corentin; Rached, Brigitte; Pourcher, Valérie; Rioux, Christophe; Vallois, Dorothée; et al. (Emerging infectious diseases, 2025)
High-dose isoniazid is recommended to treat multidrug-resistant tuberculosis (MDR TB). Among 958 MDR TB isolates identified in France during 2008-2022, 93.1% exhibited high-level isoniazid resistance, and molecular testing showed limited diagnostic accuracy in predicting resistance. Clinicians should reconsider using high-dose isoniazid in MDR TB treatment because of suboptimal effect and toxicity concerns.